Deoxydehydration of glycerol in presence of rhenium compounds: reactivity and mechanistic aspects. Issue 12 (10th May 2019) - Lupacchini, Massimiliano; Mascitti, Andrea; Canale, Valentino; Tonucci, Lucia; Colacino, Evelina; Passacantando, Maurizio; Marrone, Alessandro; d'Alessandro, Nicola
Abstract : Re compounds in different oxidation states are activated during a delay time into an active Re alkoxide precipitate catalysing the DODH of glycerol. Abstract : Allyl alcohol (AA) was obtained by the deoxydehydration (DODH) of glycerol performed in the presence of a number of Re compounds (oxides, phosphine and halide derivatives) in alcoholic solvent or in neat conditions. Independently of starting Re species, the resulting catalytic process featured a delay time, necessary to start the formation of both AA and an Re-alkoxide precipitate. However, no delay time was detected by operating DODH using a preformed precipitate obtained by either Re source. As a consequence, and based on IR spectral analysis, it was hypothesized that the Re precipitate is the actual catalyst of DODH. The mechanism of DODH catalysis operated by methyltrioxorhenium (MTO) was studied by experimental and theoretical approaches. The results suggest that MTO releases methane with the formation of an Re VII alkoxide that subsequently aggregates by yielding the precipitate. The Re VII centre precipitate surface then undergoes reduction by forming Re V catalytic spots. The calculated kinetics also indicate that the detected latency can be ascribed to the presence of two high barriers, i.e. methane release and Re VII → Re V reduction, whereas the downstream processes, i.e. glycation and AA release, are not rate determining.